2008
DOI: 10.1071/mf07192
|View full text |Cite
|
Sign up to set email alerts
|

Molecular barcoding of north-east Atlantic deep-water sharks: species identification and application to fisheries management and conservation

Abstract: Two genera of elasmobranchii, Centrophorus and Centroscymnus, include species that represent the highest landings of deep-water sharks caught by fishing fleets operating in the north-east Atlantic. There are morphology-based identification problems among and within genera, and landings of processed shark products further prevent an objective assessment of these species. The present study is the first attempt to test the suitability of using a DNA barcode approach to discriminate accurately among the four most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 25 publications
7
34
1
Order By: Relevance
“…The mean of the pairwise differences between specimens of C. granulosus and those of C. squamosus was 37.8. A similar lack of divergence between these two species was reported by Moura et al (2008).…”
Section: Centrophoridae (Gulper Sharks)supporting
confidence: 63%
See 2 more Smart Citations
“…The mean of the pairwise differences between specimens of C. granulosus and those of C. squamosus was 37.8. A similar lack of divergence between these two species was reported by Moura et al (2008).…”
Section: Centrophoridae (Gulper Sharks)supporting
confidence: 63%
“…The average of the pairwise differences between C. owstonii and C. coelolepis was 74.7 (or 7.15%). This result is somewhat more conservative than that of Moura et al (2008) who found the genetic divergence between these two species to be 12.8%.…”
Section: Somniosidae (Sleeper Sharks) In Partcontrasting
confidence: 46%
See 1 more Smart Citation
“…The identification of early life stages, such as larvae and transforming young, is essential for current studies on the distribution and reproductive strategies of pelagic fishes (Takeyama et al 2001, Moura et al 2008, Valdez-Moreno et al 2010. Thus, the assessment of biodiversity and its implication in the management of vulnerable marine ecosystems requires an accurate taxonomic assignment of fish larvae.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the amplified fragments from cox1 gene did not provided enough information to establish phylogenetic relationships in the species studied; mainly due to the use of technologies now considered obsolete, their inability to develop species-specific primers, and the inherent evolutionary close-proximity of longnose skates (Díaz de Astarloa et al, 2008;Naylor et al 2012a, b;Vargas-Caro et al, 2015, 2017. Sequences of all mitochondrial loci amplified in the present study showed over 98% identity and a low number of -82-based on morphology Moura et al, 2008;Toffoli et al, 2008;Ward et al, 2005Ward et al, , 2007Ward et al, , 2008Ward et al, , 2009Wong et al, 2009;Zemlak et al, 2009). Numerous studies have demonstrated the efficacy of using cox1 and nadh2 as diagnostic sequences for universal species identification in animal lineages, and the discordance between cox1 and nadh2 analysis was unexpected.…”
Section: Molecular Tools For Longnose Skates Identificationmentioning
confidence: 98%